Beliefs in “Brilliance” and Belonging Uncertainty in Male and Female STEM Students - Deiglmayr, Anne; Stern, Elsbeth; Schubert, Renate (Frontiers in Psychology, 2019)
A wide-spread stereotype that influences women’s paths into STEM (or non-STEM) fields is the implicit association of science and mathematics with “male” and with requiring high levels of male-associated “brilliance”. Recent research on such “field-specific ability beliefs” has shown that a high emphasis on brilliance in a specific field goes along with a low share of female students among its graduates. A possible mediating mechanisms between cultural expectations and stereotypes on the one hand, and women’s underrepresentation in math-intensive STEM fields on the other hand, is that women may be more likely than men to feel that they do not belong to these fields. In the present study, we investigated field-specific ability beliefs as well as belonging uncertainty in a sample of n= 1294 male and female university students from five STEM fields (Mathematics, Physics, Computer Science, Electrical Engineering, and Mechanical Engineering) at a prestigious technical university in Switzerland. Field-specific ability beliefs of both men and women emphasized brilliance more in some fields (Mathematics, Physics) than in others (Engineering). Women showed higher beliefs in brilliance than men did, and also reported higher levels of belonging uncertainty. For both genders, there was a small, positive correlation (r=.19) of belief in brilliance and belonging uncertainty. Our results show that even among young women who have chosen to study a STEM subject, the implicit bias linking science to male-associated “brilliance” appears to be prevalent. This implicit bias is likely to affect these women’s feeling of belonging to their chosen fields, and ultimately their studying behaviour and academic success.